Analisis Kinerja Keuangan Sebelum dan Sesudah Transformasi Digital - Ginting, Wenny Anggeresia; Nasution, Siti Aisyah; Pangemanan, Shane Anneke (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to analyze the financial performance of trading sector companies listed on the Indonesia Stock Exchange for the period 2012-2015 (before digital transformation) and 2017-2020 (after digital transformation). This study used a quantitative descriptive method and a population of 144 companies. The sampling technique used purposive sampling and obtained 98 trading sector companies. The data analysis technique used Paired Sample T-Test analysis. The results of the study indicate differences in the financial performance of companies in the trading sector before and after digital transformation as measured by the return on asset ratio, total asset turnover, and debt ratio on the Indonesia Stock Exchange.